Prabu Brawijaya Spiritual Characteristics in Tari Brawijaya - Andika Putra Pradana; Scarletina Vidyayani Eka (Universitas Brawijaya, 2020)
Dance, in particular, demonstrates a semiotic process. This happens in dance when choreographic signs, such as ritualistic, magical, or religious movement expressions, are encoded. Dance